PENATALAKSANAAN FISIOTERAPI PADA FROZEN SHOULDER ETCAUSA CAPSULITIS ADHESIVA DEXTRA DENGAN MODALITAS AUTO STRETCHING DAN MUSCLE ENERGY TECHNIQUE - Rifke Iddatu Iddatuzzahni (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
Background : Frozen shoulder is also known as adhesive capsulitis which is characterized by pain and limited movement of the shoulder joint. Frozen shoulder is caused by inflammation of the glenohumeral joint capsule with the rotator cuff, subacromial bursa, and deltoid. The inflammation causes a decrease in synovial fluid, thickening and swelling in the joint capsule area so that it will reduce the joint connection and cause joint pain and stiffness. This writing aims to determine the management of Auto Streatching and Muscle Energy Techniques in overcoming problems in these patients. The method used is a case study method with 1 respondent using a Shoulder Pain Index Disability (SPADI) measuring instrument aimed at measuring the ability of functional activities. 5 times therapy in 2 weeks can reduce pain, increase muscle strength and increase joint range of motion in Frozen Shoulder patients etcausa capsulitis Adhesive The conclusion of this paper is that Auto Streatching and Muscle Energy Techniques can reduce pain, increase muscle strength, and increase the range of motion of joints in Frozen cases. Shoulder etcausa capsulitis Adhesive Keywords: Frozen shoulder capsulitis adhesive, Auto streatching, Muscle energy technique, Shoulder pain index disability